The Versova Koli Seafood Festival - Mumbai Archive Project Team (Jio Institute, 2024)
The Versova Koli Seafood Festival provides a platform for Koli women to showcase their culinary skills and promote the seafood delicacies that are an integral part of their culinary traditions. It also offers visitors the opportunity to contribute to the local economy and support sustainable livelihoods by purchasing seafood, handicrafts, and other products directly from Koli vendors and artisans.